Acute exacerbations of COPD are associated with a prothrombotic state through platelet-monocyte complexes, endothelial activation and increased thrombin generation. (September 2020) - van der Vorm, Lisa N.; Li, Li; Huskens, Dana; Hulstein, Janine J.J.; Roest, Mark; de Groot, Philip G.; ten Cate, Hugo; de Laat, Bas; Remijn, Jasper A.; Simons, Sami O.
Abstract: Introduction: Patients with chronic obstructive pulmonary disease (COPD) are at increased risk for cardiovascular events, particularly following an acute exacerbation (AE-COPD). Exacerbations are associated with increased systemic inflammation, which may drive coagulation. This prospective cohort study aimed to determine how an AE-COPD affects platelet activation, the endothelium, plasmatic coagulation and fibrinolysis, and its association with systemic inflammation. Materials and methods: Fifty-two patients with an AE-COPD were included. Blood samples at admission, at day 3 of treatment and at convalescence were available for 32 patients. Platelet-monocyte complex (PMC) formation, monocyte Mac-1 expression and platelet (re)activity (P-selectin expression, αIIbβ3 activation) were measured by flow cytometry. Von Willebrand Factor (VWF), thrombin generation (TG) and clot lysis time (CLT) were determined as measures of endothelial activation, plasmatic coagulation and fibrinolysis, respectively. Results: Exacerbations were associated with increased PMCs (MFI 31.3 vs 23.8, p = 0.004) and Mac-1 (MFI 38.2 vs 34.8, p = 0.006) compared to convalescence, but not with changes in platelet (re)activity. VWF (antigen, activity, active fraction) and TG (peak, ETP and velocity index) were all significantly higher during AE-COPD compared to convalescence. PMCs, Mac-1, VWF and TG were positively associated with systemic inflammation (CRP). CLT was prolonged in AE-COPD patients with systemic inflammation. Moreover, platelet hyperreactivity on admission was associated with an increased risk for exacerbation relapse. Conclusions: Acute exacerbations are associated with an inflammation-associated prothrombotic state, characterized by increased PMCs, endothelial activation and plasmatic coagulation. Our findings provide direction for future studies on biomarkers predicting the risk of exacerbation relapse and cardiovascular events. Highlights: Acute exacerbations of COPD (AE-COPD) pose an increased thrombotic risk. AE-COPDs were associated with increased PMCs, (active) VWF and thrombin generation. The prothrombotic changes during AE-COPD were associated with systemic inflammation. Future biomarker studies that could guide thromboprophylaxis in AE-COPD are needed.